Selection of gamma analysis acceptance criteria in IMRT QA using Gafchromic EBT3 film dosimetry. Issue 2 (3rd December 2018) - Isa Khan, Muhammad; Shakil, Muhammad; Tahir, Muhammad Bilal; Rafique, Muhammad; Iqbal, Tahir; Zahoor, Aliza; ur Rehman, Jalil; Iqbal, Khalid; Chow, James C. L.
Abstract: Background and purpose: This study reported the justification and selection of acceptable γ criteria with respect to low (6 MV) and high (15 MV) photon beams for intensity-modulated radiation therapy quality assurance (IMRT QA) using the Gafchromic external beam therapy 3 (EBT3) film. Materials and methods: Five-field step-and-shoot IMRT was used to treat 16 brain IMRT patients using the dual-energy DHX-S linear accelerator (Varian Medical System, Palo Alto, CA, USA). Dose comparisons between computed values of the treatment planning system (TPS) and Gafchromic EBT3 film were evaluated based on γ analysis using the Film QA Pro software. The dose distribution was analysed with gamma area histograms (GAHs) generated using different γ criteria (3%/2 mm, 3%/3 mm and 5%/3 mm) for the 6 and 15 MV photon beams, to optimise the best distance-to-agreement (DTA) criteria with respect to the beam energy. Results: From the comparison between the dose distributions acquired from the TPS and EBT3 film, a DTA criterion of 3%/2 mm showed less dose differences (DDs) with passing rates up to 93% for the 6 MV photon beams, while for the 15 MV a relaxed DTA criterion of 5%/3 mm was consistent with the DD acceptability criteria with a 95% passing rate. Conclusions: Our results suggested that high-energy photon beams required relaxed DTA criteria for the brain IMRT QA, while low-energy photon beams showed better results even with tight DTA criteria.